PENERAPAN LAYANAN BIMBINGAN KLASIKAL MELALUI TEKNIK SOSIODRAMA TERHADAP PERILAKU AGRESI - Syifani Aulia Pratiwi; Heris Hendriana; Reza Pahlevi (IKIP Siliwangi, 2022)
The background of this research is the current pandemic of covid-19 that affected giving service classical guidance in the school. The aim of this research is to know the application of classical guidance services through sociodrama techniques on aggression behavior. The method used in this research is descriptive qualitative research method. The instruments of this research used data from observation, interviews, and documentation. The subject premier of this research is teacher of guidance and counseling, and students of SMP Negeri 4 Cipatat grade Eight. The secondary subject of this research is the data from the school, such as from the Head School of SMP Negeri 4 Cipatat, the homeroom teacher, and the teacher of guidance and counseling. The results showed that after the giving activity of service classical guidance online through sociodrama technic to the aggression behavior of students, it works well. It can be seen from the capability of the teacher guidance and counseling in applying all stages in the service of classical guidance, starting from the beginning of implementation until finishing or evaluating. Keywords: Classical Guidance, Sociodrama Technic, Aggression Behavior